Discussions on School Reform - a Long Way to the Unification of Schools for 10 to 14-Year-Olds - Seebauer, Renate (Revija za elementarno izobraževanje, 2009)
The beginning of the article presents a retrospect of the discussion of unifying schools in Austria with arguments for and against them. In the 2008/09 school year a few selected Austrian regions started experimental school models in an attempt to unify their school system at the level of ten to fourteen-year-old pupils. More schools will start similar experiments a year later. Particularism — mainly politically motivated — has become evident: Nine regions, nine concepts. The fact that a new school organization will need teachers that have been educated in line with the new pedagogical concepts has been discussed sporadically. It remains neglected, however, in the overall concept of educational reform — at least in current public discussions.